Search for the doubly heavy Ξ0bc baryon via decays to D0pK−; Journal of High Energy Physics; Vol. 2020, iss. 11 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen